FAKTOR PENYEBAB KERUSAKAN ALUR(RUST) PADA LAPISAN PERKERASAN JALAN - Sumiati Sumiati (PILAR, 2012)
One of the factor causing road damage that often occurs and can had to futher damage the groves without any cracks. This damage will be examined using the four samples taken from drill cores in a way that develoving cracks in street groove without cracks.  The sample is then carried out the testing of physical properties and testing of Marshall.The result showed that the factors that cause, such as: asphalt concrete mixtures by using asphalt concrete that’s too small, insufficient in weighing aggregate, because too much use of fine-grained aggregate and the amount of sand used is greater than fifteen percent, which is not in accordance with the specifications required. This resulted in unstable asphalt concrete mixtures, so that when traversed by vehicle will cause the grooves that made an impression of vehicle wheels.